Firm size and cost system sophistication: The role of firm age. Issue 2 (March 2022) - Hadid, Wael; Hamdan, Mohammed
Abstract: The costing literature has failed to conclusively explain why some companies implement sophisticated costing systems while others do not. Although some contingency variables were proposed, inconclusive results were reported which raised concerns about their underlying theory. Focusing on firm size, as the most examined and confusing variable in this contingency literature, we develop and test more complex relations than in prior studies to provide more insights into its role. More specifically, we test potential indirect positive relations between firm size and cost system sophistication (through product diversity and cost structure) and bring to light the role of firm age largely neglected in the cost accounting literature. Using two different statistical analyses (i.e. SEM and PLS) and data from manufacturing firms, our findings suggest, in contrast to the majority of prior studies, that not all larger firms should be expected to have sophisticated costing systems. The impact of firm size on cost system sophistication depends on firm age and is mediated by product diversity but not cost structure. We conclude by emphasizing the need for more complex models to further advance the theory on costing systems. Such models should go beyond explaining the potential impact of each contextual variable in isolation.